Direct oxidative lactonization of alkenoic acids mediated solely by NaIO4: beyond a simple oxidant. Issue 36 (14th April 2016) - Kang, Yan-Biao; Chen, Xian-Min; Yao, Chuan-Zhi; Ning, Xiao-Shan
Abstract : Triflic acid-catalyzed direct oxidative lactonization of alkenoic acids mediated solely by NaIO4 without halogen salts is described. Abstract : Triflic acid-catalyzed direct oxidative lactonization of alkenoic acids mediated solely by NaIO4 without halogen salts is described. Sodium periodate works not only as an oxidant, but also as an active reagent and directly mediates the lactonization. A new cheap, green, and practical oxidative lactonization approach has been developed using NaIO4 as the sole reagent.